2018
DOI: 10.1007/s00128-018-2365-x
|View full text |Cite
|
Sign up to set email alerts
|

Contamination Level and Spatial Distribution of Heavy Metals in Water and Sediments of El Guájaro Reservoir, Colombia

Abstract: Heavy metals have become a subject of special concern worldwide, mainly due to high persistence in the environment, toxicity, biogeochemical recycling and ecological risk. Therefore, the objective of this investigation was to analyze the spatial-temporal distribution of heavy metals in water and sediments to determine the environmental status of El Guájaro Reservoir, where such studies have not been developed. Two measurement campaigns (dry and wet period) were carried out and eight sampling stations were sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“…This result corroborate the high concentration of Zn in comparison with the others HM. Additionally, Torregroza-Espinosa et al. (2018), reported the presence of HM (Zn, Pb, and Hg) in water and surface sediments of El Guájaro Reservoir, the highest levels were found in the southwest and northern zones of this body of water, it is possible that the pollutants are associated with agricultural and mining activity, floodgate (El Guájaro Reservoir with Repelón ID) and the connection with the Canal del Dique (from Magdalena river) (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…This result corroborate the high concentration of Zn in comparison with the others HM. Additionally, Torregroza-Espinosa et al. (2018), reported the presence of HM (Zn, Pb, and Hg) in water and surface sediments of El Guájaro Reservoir, the highest levels were found in the southwest and northern zones of this body of water, it is possible that the pollutants are associated with agricultural and mining activity, floodgate (El Guájaro Reservoir with Repelón ID) and the connection with the Canal del Dique (from Magdalena river) (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…In their study, higher heavy metal concentrations were recorded in rainy season for both water and sediment than in dry season, except for Pb and Cd, which had higher sediment concentrations in the dry season. Also, [31] in their research, which detected concentrations of heavy metals in water and sediments from the El Guájaro Reservoir, it was found that Pb and Hg were not detected in the surface waters of El Guájaro reservoir during the dry season, nor was zinc detected during the wet season; however, the highest concentrations of heavy metals were observed during the wet season. [31] and [22] avers that the concentration of heavy metals varies with seasons.…”
Section: Introductionmentioning
confidence: 94%
“…Posteriormente se molieron en mortero de ágata y los materiales resultantes se codificaron y almacenaron en recipientes herméticos de plástico para su posterior análisis, siguiendo el mismo protocolo para el sustrato hospedero. Las muestras de sedimento se homogenizaron y se secaron hasta peso constante en un horno con circulación de aire a 50 °C y tamizándose a 2 mm (Moyano et al, 2010;Torregrosa-Espinoza et al, 2018). Los contenidos de metales pesados fueron determinados por espectrofotometría de absorción atómica, con llama de aire-acetileno (Mn, Ni, Cr, Co), vapor frío (Hg) y mediante voltametría (Pb, Cd, Cu, Zn).…”
Section: Fase De Laboratoriounclassified